Anthropological Studies on South Asian Pilgrimage: Case of Buddhist Pilgrimage in Sri Lanka - De Silva, D. A. Premakumara (The international journal of religious tourism and pilgrimage, 2016)
Anthropological studies relating to South Asian pilgrimage have been of several types. Interest in the field can be traced back to at the time when Victor Turner was writing on this subject (notably, the works of Vidyarthi, 1961, 1979; Jha, 1985, 1995; Bhardwaj, 1973 and; Bharati, 1970). Among the relevant ethnographies for South Asia there are a number of studies which mainly concentrate on describing a pilgrimage centre or sacred place. In general, the emphasis of these studies is on priests, the organization of the pilgrim centres, and other occupants of the pilgrimage centres; in other words, they are more sacred place' oriented rather than focussing on the pilgrims themselves. The pilgrimage literature for South Asia, in general, lends greater support to the competing discourse perspective than to the Turnerian approach. However, most academic studies of pilgrimage in South Asia have concentrated on the explicitly religious domain, on the major religious traditions and on regional pilgrimage cults, and has placed far less emphasis on pilgrimage in secularized contexts such as the pilgrimage service economy, that has grown around pilgrimage centres, politics, nationalism, ethnicity, gender, pilgrimage sites associated with dead cultural heroes, touristic dimensions of pilgrimage, educational visits to sacred and historic locations, or simply pilgrimage for the sake of journeying (for fun'). Anthropological studies of pilgrimage in Sri Lanka mainly derive theoretical orientation from the functionalist approach (Obeyesekere, 1966, 1978, 1981; Evers, 1972; Seneviratne, 1978). However, more recent studies by Pfaffenberger (1979), Nissan (1985, 1988), Stirrat (1982, 1991, 1992), Whitaker (1999), and Bastin (2002), mainly put their theoretical arguments against a universalistic' perspective and emphasise the importance of considering multiple historical representations of Buddhist pilgrimage centres in Sri Lanka, rather than studying them as a unified tradition. In this paper I will attempt to break down the boundaries around the anthropology of pilgrimage, questioning the dubious division between structure (e.g., Turnerian view), and process (e.g., competing discourse), religion and politics, and this and other worldly formulations. These dominant views in the anthropology of pilgrimage are tested with my ethnographical and historical materials particularly in relation to the Sri Pāda (Adam's Peak) pilgrimage site and the pilgrims journeying to it. I would argue with my findings that it is hard to grasp an overall picture about the pilgrimage site, as well as the journey to it in the context of Buddhist pilgrimage in Sri Lanka, if too much emphasis is placed on either theoretical perspective.